A taxonomic review of the genus Paracoccidioides, with focus on the uncultivable species. - Raquel Vilela; Sybren de Hoog; Konstanze Bensch; Eduardo Bagagli; Leonel Mendoza (Public Library of Science (PLoS), 2023)
Paracoccidioides species have always been surrounded by taxonomic uncertainties. The continuing nomenclatoral muddle was caused in part by the failure of Adolfo Lutz and Jorge Lôbo to name the etiologic agents of human paracoccidioidomycosis and Jorge Lôbo's diseases, respectively. Early in their history, it was postulated that the cultivable species causing systemic infections belonged in the genus Paracoccidioides, whereas the uncultivable species, causing skin disease, were not part of the genus. The taxonomy of these pathogens was further complicated when a similar skin disease with numerous yeast-like cells in infected dolphins was also reported. Due to its phenotypic similarities with that described by Jorge Lôbo in human and its uncultivable nature, it was assumed that the disease in dolphins was caused by the same fungus. Recent molecular and population genetic analysis, however, found the DNA extracted from the uncultivable yeast-like cells affecting dolphins shared common phylogenetic traits with cultivable Paracoccidioides species. The study revealed that the uncultivable pathogens comprised 2 different Paracoccidioides species, now known as P. ceti and P. loboi, correspondingly. To validate P. loboi binomial, a comprehensive historical critical review of Jorge Lôbo etiology was performed. This review showed the proposed binomial P. loboi was previously used, and, thus, a replacement name is introduced, Paracoccidioides lobogeorgii nom. nov. In addition, in this review, several cultivable human Paracoccidioides species are validated, and the generic type species, P. brasiliensis, is neotypified as the original material could not be traced.